Internal migration and rural service provision in northern Ghana - Wouterse, Fleur Stephanie (International Food Policy Research Institute, 2010)
This paper uses a two-stage conditional maximum likelihood procedure and new data from Ghana to identify the determinants of rural-urban migration at the individual, household and community levels, with a particular focus on rural services. The econometric evidence supports the theoretical expectation that human-capital and network variables as well as assets are important determinants of migration. Taking the possible endogeneity of rural services into account, the evidence suggests that rural service improvements aimed at reducing economic isolation can enhance labor mobility and free up on-farm labor for migration by lowering transaction costs.